"Just because we can, should we?" Biometrics Institute launches ethical campaign. (April 2019) - Unknown
Abstract : The Biometrics Institute has called on its 240 member organisations worldwide to rein back their use of biometric systems and act ethically under the slogan "Just because we can, should we?".